2021
DOI: 10.1038/s41598-020-80248-7
|View full text |Cite
|
Sign up to set email alerts
|

Geographical influences on thyroid abnormalities in adult population from iodine-replete regions: a cross-sectional study

Abstract: The studies on the increasing incidence of thyroid abnormalities are scarce. The aim of this current study was to ascertain the effects of geographical region on thyroid abnormalities under the context of universal salt iodization (USI). We randomly selected 1255 participants residing in inland and 1248 in coast, with the determination of urinary iodine concentration (UIC) and functional and morphological abnormalities of thyroid gland. The median UIC was significantly higher for the inland participants (188.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…The percentage of hypothyroidism was significantly higher for the participants from the inland (17.5%) than those from the coast (7.2%; p < 0.001). 38 A survey in Shanghai, China, yielded similar results. 39 We also found this phenomenon for both OH and SCH.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The percentage of hypothyroidism was significantly higher for the participants from the inland (17.5%) than those from the coast (7.2%; p < 0.001). 38 A survey in Shanghai, China, yielded similar results. 39 We also found this phenomenon for both OH and SCH.…”
Section: Discussionmentioning
confidence: 70%
“…Another study in China found the median UIC for the participants from the inland (188.5 µg/L) was significantly higher than those from the coast (128.5 µg/L; p < 0.001). The percentage of hypothyroidism was significantly higher for the participants from the inland (17.5%) than those from the coast (7.2%; p < 0.001) 38. A survey in Shanghai, China, yielded similar results 39.…”
Section: Discussionmentioning
confidence: 75%
“…Subclinical and overt thyroid dysfunction are common diseases of the endocrine system. The incidence rates vary across different regions, with the coastal population having a higher risk of developing thyroid abnormalities compared to inland areas ( Wang et al, 2021 ). Genetic susceptibility is closely associated with the onset of thyroid diseases, such as autoimmune thyroid diseases (AITD) ( Medici et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the study population was not nationally representative, since participants were primarily recruited among the university staff, mainly from coastal urban areas, with a high level of education, and included fewer smokers than the general population. Regional divergence, with proximity to the coastal zone and rural areas associated with the iodine status, has been reported, including in Portugal [ 6 , 7 , 62 , 63 ]. Also, participants with a higher level of education were more likely to have better socio-economic status and therefore be more prone to a healthy diet.…”
Section: Discussionmentioning
confidence: 99%